Dual‐Programmable Shape‐Morphing and Self‐Healing Organohydrogels Through Orthogonal Supramolecular Heteronetworks. Issue 51 (17th October 2018) - Zhao, Ziguang; Zhuo, Shuyun; Fang, Ruochen; Zhang, Longhao; Zhou, Xintao; Xu, Yichao; Zhang, Jianqi; Dong, Zhichao; Jiang, Lei; Liu, Mingjie
Abstract: Programmable materials that can change their inherent shapes or properties are highly desirable due to their promising applications. However, among various programmable shape‐morphing materials, the single control route allows temporary states to recover the unchangeable former state, thus lacking the sophisticated programmability for their shape‐encoding behaviors and mechanics. Herein, dual‐programmable shape‐morphing organohydrogels featuring supramolecular heteronetworks are developed. In the system, the metallo‐supramolecular hydrogel framework and micro‐organogels featuring semicrystalline comb‐type networks independently respond to different stimuli, thereby providing orthogonal dual‐switching mechanics and ultrahigh mechanical strength. The supramolecular heteronetworks also possess excellent self‐healing properties. More notably, such orthogonal supramolecular heteronetworks demonstrate hierarchical shape morphing performance that far exceeds conventional shape‐morphing materials. Utilizing this dual programming strategy of the orthogonal supramolecular heteronetworks, the material's permanent shape can be manipulated in a step‐wise shape morphing process, thereby realizing sophisticated shape changes with a high degree of freedom. The organohydrogels can act as a biomimetic smart device for the on‐demand control of unidirectional liquid transport. Based on these characteristics, it is anticipated that the supramolecular organohydrogels may serve as adaptive programmable materials for a variety of applications. Abstract : Dual‐programmable shape‐morphing organohydrogels feature supramolecular orthogonal heteronetworks. The metallo‐supramolecular hydrogel framework and micro‐organogels featuring semicrystalline networks independently respond to different stimuli, providing orthogonal dual‐switching mechanics, ultrahigh mechanical strength, and self‐healing properties. Such heteronetworks demonstrate sophisticated hierarchical shape changes with a high degree of freedom. Thus, the organohydrogels act as biomimetic smart devices for the on‐demand control of unidirectional liquid transport.